Neurodynamics of up and down Transitions in Network Model - Xuying Xu; Rubin Wang (Abstract and Applied Analysis)
This paper focuses on the neurodynamical research of a small neural network that consists of 25 neurons. We study the periodic spontaneous activity and transitions between up and down states without synaptic input. The results demonstrate that these transitions are bidirectional or unidirectional with the parameters changing, which not only reveals the function of the cortex, but also cohere with the experiment results.